A Novel Transformation Electromagnetic Theory-Based Coverage Optimization Method for Wireless Network. (4th November 2013) - Li, Yuanxuan; Zhu, Gang; Lin, Siyu; Guan, Ke; Li, Yan
Abstract : Improving the reliability of the radio coverage in shadow area is always an important issue for the wireless communications. The emergence of the transformation electromagnetic (TE) technique provides a new method to control the propagation direction of the radio signal. This paper proposes a coverage optimization method based on the TE technique; a cloak which covers the surface of obstacle is designed to improve the coverage performance in shadow area. The material parameters of cloak are calculated by the transformation electromagnetic method. To solve the calculation problem for the rectangular obstacle, the Fourier series is used to approximately describe the rectangular boundaries. The effectiveness of the proposed cloak for the coverage optimization is validated by the theoretical analysis and simulation results. The simulation results show that the coverage performance can be improved significantly.